Hakikat Pendidikan Islam: Telaah Mengenai Dasar, Tujuan, dan Kurikulum Pendidikan Islam Serta Implementasinya dalam Lembaga Pendidikan Islam: Penelitian - Maharani, Ria; Junaidi, Junaidi; Arif, Armai; Zalnur, Muhammad; Nasution, Nurul Annisa Dewantari; Abimayu, Riman (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Islamic education plays a central role in building human civilization and shaping a complete Muslim personality (kaffah). This paper aims to examine the nature, foundation, objectives, and curriculum of Islamic education, as well as its implementation in educational institutions. The essence of Islamic education is defined as a conscious, planned, and continuous effort to develop physical, intellectual, and spiritual potential based on the Qur'an and Hadith. Its primary foundation is based on the revelation of Allah and the Sunnah of the Prophet Muhammad as a guide to life. The goal of Islamic education is to form a perfect human being who possesses a balance between faith, knowledge, and good deeds, and is able to fulfill his function as a servant of Allah ('abdullah) and caliph on earth. The applied curriculum is integrative and holistic, combining religious and general knowledge without dichotomy. The implementation of Islamic education in institutions such as madrasas and Islamic boarding schools emphasizes exemplary behavior (uswah), habituation (ta'dib), and teaching relevant to the challenges of the times and technology.